Platelet-Derived Exosomes Affect the Proliferation and Migration of Human Umbilical Vein Endothelial Cells Via miR-126 - Sun, Yan; Liu, Xiao-li; Zhang, Dai; Liu, Fang; Cheng, Yu-jing; Ma, Yue; Zhou, Yu-jie; Zhao, Ying-xin (Current Vascular Pharmacology, 2019)
Background: Intraplaque angiogenesis, the process of generating new blood vessels mediated by endothelial cells, contributes to plaque growth, intraplaque hemorrhage, and thromboembolic events. Platelet-derived Exosomes (PLT-EXOs) affect angiogenesis in multiple ways. The ability of miR-126, one of the best-characterized miRNAs that regulates angiogenesis, carried by PLT-EXOs to influence angiogenesis via the regulation of the proliferation and migration of endothelial cells is unknown. In this study, we aimed to investigate the effects of PLT-EXOs on angiogenesis by Human Umbilical Vein Endothelial Cells (HUVECs). Methods: We evaluated the levels of miR-126 and angiogenic factors in PLT-EXOs from Acute Coronary Syndrome (ACS) patients and healthy donors by real-time Polymerase Chain Reaction (PCR) and western blotting. We incubated HUVECs with PLT-EXOs and measured cell proliferation and migration with the Cell Counting Kit-8 assay and scratch assay, respectively. We also investigated the expression of miR-126 and angiogenic factors in HUVECs after exposure to PLT-EXOs by western blotting and real-time PCR. Results: PLT-EXOs from ACS patients contained higher levels of miR-126 and angiogenic factors, including Vascular Endothelial Growth Factor (VEGF), basic Fibroblast Growth Factor (bFGF), and Transforming Growth Factor Beta 1 (TGF-β1), than those from healthy donors (p<0.05). Moreover, the levels of exosomal miR-126 and angiogenic factors were increased after stimulation with thrombin (p<0.01). HUVEC proliferation and migration were promoted by treatment with activated PLT-EXOs (p<0.01); they were accompanied by the over-expression of miR-126 and angiogenic factors, including VEGF, bFGF, and TGF-β1 (p<0.01). Conclusion: Activated PLT-EXOs promoted the proliferation and migration of HUVECs, and the overexpression of miR-126 and angiogenic factors, thereby elucidating potential new therapeutic targets for intraplaque angiogenesis.
Keywords: Intraplaque angiogenesis